Improving Just-in-Time manufacturing operations by using Internet of Things based solutions - Xu, Yuchun; Chen, M. (Elsevier, 2016)
Just in time (JIT) manufacturing is one of the main methodologies used to enhance manufacturers’ competitiveness through inventory and lead time reduction. However implementing JIT has some challenges, e.g. lack of required information sharing or communication between stakeholders, insufficient sound action or planning system etc. Internet of Things (IoT) technology has the potential to be used for acquiring data and information in real time to facilitate dynamic JIT manufacturing. This paper presents a research on using IoT based solution to enhance JIT manufacturing. The general challenges of JIT implementation are identified first, then an IoT based solution is proposed to address the JIT challenges in a selected case study. A framework to support the proposed IoT solution is developed and its implementation steps are suggested.
Keywords: Production Scheduling; Dynamic Scheduling; Real-time resource status monitoring; Just-in-Time manufacturing; Internet of Things; IoT; RFID